Mampukah Kontrasepsi Hormonal Melindungi dari Kanker Endometrium? Sebuah Tinjauan Pustaka - Kusuma, Fitriyadi (Griya Widya: Journal of Sexual and Reproductive Health, 2024)
Introduction: This review aims to summarize the protective mechanisms, effectiveness, and clinical implications of hormonal contraception in reducing endometrial cancer risk. Methods: A literature review was conducted by analyzing epidemiological studies, meta-analyses, and clinical trials focusing on the relationship between hormonal contraceptives and endometrial cancer risk. The review included studies published in major medical databases such as PubMed, Scopus, and Cochrane Library. Results: The findings indicate that COC use reduces endometrial cancer risk by 30–50%, with long-term use (≥10 years) providing up to 80% risk reduction. The protective effect persists for decades after discontinuation. Progestin-only methods, including the levonorgestrel-releasing intrauterine device (LNG-IUD) and Depo-Provera, also demonstrate substantial risk reduction by inducing endometrial atrophy and suppressing hyperplasia. The protective effects are influenced by duration of use, hormonal composition, and individual factors such as obesity and reproductive status. Discussion: Hormonal contraception represents a viable preventive strategy, particularly for high-risk populations, including women with polycystic ovary syndrome (PCOS) and Lynch syndrome. However, risks such as thromboembolism and hormone-sensitive malignancies must be considered in clinical decision-making. Conclusion: Hormonal contraceptives provide substantial long-term protection against endometrial cancer through multiple mechanisms. Personalized contraceptive strategies should be tailored to individual risk factors to maximize benefits while minimizing potential adverse effects.